Cloud based e-commerce and management systems for SME - Muhammad Azizi Fahmi, Abd Rani; Khairul Ikhwan, Ahmad Zaini; Azma, Abdullah (2021)
Cloud Based E-Commerce and Management Systems for SME is developed for a purpose to help SME user and customer to start a bussines. With the rapid development of the internet, an entrepreneur can use a system that can manage to stream from the store as the inventory management system and online shopping system to allows the user to gather centralized information for business and achieve operational efficiency and productivity.